Construction ideas of the middle platform capability operation center of telecom operators - Xin GU; Xiaorong NI; Zhao LIU; Xiaonan FANG; Yuemeng LI (Dianxin kexue)
The architecture and function of the middle platform capability operation center of telecom operators were analyzed, and the registration, encapsulation, and access control strategy of service and capability were expounded.The construction ideas of the service governance system and the capacity collaboration were discussed，and the evolution path of the middle platform capacity operation center was proposed.The proposed idea provides a valuable reference for telecom operator to build the system of middle platform.